ACL Repair: Rationale and When to Consider Over Reconstruction - Jalen N. Broome BA, MS; Rachel E. Cherelstein BS; Edward S. Chang MD (SAGE Publishing, 2024)
Background: Anterior cruciate ligament (ACL) restoration has been divided into repair versus reconstructive approaches. We present an ACL repair using FiberTape sutures as an internal brace and an adjustable cortical button fixation on the femur. Indications: ACL rupture is a condition in which restoration is essential to regaining adequate knee function. ACL repair may be indicated in patients with an acute tear (<4 weeks), Sherman classification type I or II tear, 35 years old or older, and with a mild-to-moderate activity level. Technique Description: ACL tightrope repair initially requires identification of the ACL tear. Following, there is femoral wall preparation and the creation of a drill tunnel in the femoral and tibial walls. FiberRing sutures are passed through the intact portion of the ACL as many times as desired. An ACL Tightrope is then fed through the FiberRing sutures. The ACL Tightrope and cortical button are passed through the femoral tunnel. FiberTape sutures are passed through a tibial tunnel to act as an internal brace. Range of motion and tension is assessed and adjusted as needed. Results: Patients meeting indications for ACL repair and undergoing repair via Tightrope implants may have outcomes comparable to counterparts undergoing ACL reconstruction. Patient-completed functional knee scores, such as International Knee Documentation Committee (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Lysholm, are similar between the 2 restoration techniques. However, younger patients undergoing an ACL repair appear to have a higher failure rate compared with reconstruction. Conclusion: ACL repair can be an adjuvant treatment option with acute femoral sided tears. Caution should be exercised when performing this procedure on younger, higher level athletes. In our technique, use of adjustable cortical button minimizes bone loss on femoral wall while providing adequate fixation. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.